2003
DOI: 10.1096/fj.02-0452fje
|View full text |Cite
|
Sign up to set email alerts
|

Aging enhances lymphocyte cytokine defects after injury

Abstract: Mortality and sepsis after a traumatic injury is greater in the elderly than in young individuals. The altered lymphocyte response observed to occur in healthy aged individuals is proposed to be a contributing factor to increased mortality. The immune response associated with the increased mortality was explored using a murine scald injury model. In the absence of injury, aged mice had depressed delayed-type hypersensitivity (DTH) and splenocyte proliferative responses relative to young mice. There was also an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 58 publications
3
29
0
1
Order By: Relevance
“…In animal models, aged mice have a higher mortality rate than young adult mice following 15% TBSA [108]. Aged mice also demonstrate significant decreases in DTH responses, Con A-stimulated splenocyte proliferation, and increases in IL-4 and IL-10 production suggesting a shift to a Th2 immune response [109]. Several studies were performed looking at the immune response following burn injury in young adult and aged mice.…”
Section: Burn and Co-morbidity Factorsmentioning
confidence: 99%
“…In animal models, aged mice have a higher mortality rate than young adult mice following 15% TBSA [108]. Aged mice also demonstrate significant decreases in DTH responses, Con A-stimulated splenocyte proliferation, and increases in IL-4 and IL-10 production suggesting a shift to a Th2 immune response [109]. Several studies were performed looking at the immune response following burn injury in young adult and aged mice.…”
Section: Burn and Co-morbidity Factorsmentioning
confidence: 99%
“…This improved survival was accompanied by a diminution in the serum levels of IL-6 . Additionally, we have reported that estrogen treatment partially restored the delayed-type hypersensitivity response , a systemic cellular immune response previously described to be markedly attenuated in aged mice after burn injury (Kovacs et al, 2002;Plackett et al, 2003).…”
Section: Discussionmentioning
confidence: 68%
“…1 The lack of an adequate amount of Th1 cytokines shortly after injury in the aged mice may parallel the increased incidence of sepsis and death that occurs in aged burn patients. 22 Therefore, altered lymphocyte response observed in healthy aged individuals may be a contributing factor to increased mortality. SAMP8 mice show markedly low NK activity, in vitro anti-SRBC antibody responses, cell proliferation, and IL-2 production, as early as two months after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Since an adequate amount of Th1 cytokines is critical to host defense in the aged animals, 22 the supplementation with nanonized black soybean might provide a benefi cial effect by favoring Th1 response in SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%